Avaliação de riscos ambientais do uso de agrotóxicos na produção da cana-de-açúcar (Saccharum officinarum l) em Xinavane – Moçambique - (:unkn) unknown (Universidade Federal do Amazonas, 2014)
The sugarcane production in Southern Mozambique has gradually increased in the last 15 years, as a result of the involvement of the population in the productive process, commanded by the Xinavane’s sugar agroindustry. Therefore, the production is been taken with massive use of pesticides, which constitutes a threat to the human and environmental health. As a result, the research has as main objective to assess the environmental hazards resultants of the use of pesticides in the sugarcane production in the region of Xinavane, located in the province of Maputo, in Mozambique, by the analysis of the factors and conditionings which determinates the method of usage of these substances and to the perception of the associated risks of using them. As the producers are majorly organized in associations, the research has observed seven associations and one individual property, where have been applied forms to the workers who deals with the chemicals, making possible the gathering of information referred to the diagnosis of the usage of these substances. To elaborate the forms were adopted the research methodology KAP (knowledge, attitude and practice), based in qualitative and quantitative social research methodology. The determination of exposure levels where made by the mathematic algorithm and to evaluate the environmental risk was used the indicator EPRIP (Environmental Potential Risk Indicator for Pesticides). The strategies adopted by the worker have resulted in low levels of occupational exposition, as result of the technical assistance and orientations and the drills offered by the agroindustry. Of the 11 pesticides used, MSMA has presented intermediary levels of environmental risks in all studied items, while the Pendimenthalin and the Glyphosate where classified as presenting no risks. In the field of environmental compartments, the subterranean waters were vulnerable. However, this research shows clearly the needs of establishing vigilance, supervision and promoting health programs, once is known the risks pesticides use, even though are being offered orientation about the substances management.
Keywords: Agricultura; Cana-de-açúcar; Agrotóxico; Exposição Ocupacional; Avaliação de Risco Ambiental; Agriculture; Sugarcane; Pesticides; Occupational Exposure; Environmental Risks Assessment; CIÊNCIAS AGRÁRIAS